IMPLEMENTASI SISTEM KNOWLEDGE MANAGEMENT UNTUK MENINGKATKAN PEMBELAJARAN ORGANISASI DI LEMBAGA PENDIDIKAN - Ahmad Jet Alamin A; Adrian K. Tarigan; Hulman Wasi Boangmanalu (Nusantara Hasana Journal, 2024)
This Community Service Program aims to implement a Knowledge Management (KM) System to enhance organizational learning in educational institutions through structured knowledge management: acquisition, documentation, storage, sharing, and utilization. Common challenges faced by partners include tacit knowledge held by individuals, scattered learning materials, undocumented best practices, and non-standard onboarding processes for new teachers and staff. Interventions are carried out through knowledge audits, KM architecture design (process–role–technology), development of taxonomies and SOPs, establishment of digital repositories and communities of practice, user training, and go-live support. Outputs include a KM blueprint, a knowledge portal/repository, standard document templates, user guides, and organizational learning KPIs.